Revision of the genus Oxytelus Gravenhorst (Staphylinidae: Oxytelinae) in Southeast Asia - Lü, Liang; Zhou, Hong-Zhang (Zootaxa, 2015)
Oxytelus species are widespread over all continents except Antarctica. Southeast Asia is one of the biodiversity hotspots in the world. In this paper, we review the Oxytelus species currently known from Southeast Asia. Seven species are described as new to science: O. castaneus sp. nov. (Vietnam), O. finitimus sp. nov. (Laos), O. grandiculus sp. nov. (Malaysia, Indonesia, and Thailand), O. insulanus sp. nov. (Malaysia and Indonesia), O. lompobatangensis sp. nov. and O. poecilopterus sp. nov. (Indonesia), and O. sublividus sp. nov. (Vietnam and Laos). Seven new synonymies are proposed: O. ruptus Fauvel = O. sublucidus Cameron, O. lucens Bernhauer = O. malaisei Scheerpeltz, O. puncticeps Kraatz = O. (Anotylus) micantoides Scheerpeltz, O. subferrugineus Cameron = O. kedirianus Cameron, O. megaceros Fauvel = O. kalisi Bernhauer, O. subincisus Cameron = O. fruhstorferi Cameron, O. antennalis Fauvel = O. cheesmani Bernhauer. Lectotypes are designated for the following names: O. armiger Fauvel, O. bellicosus Fauvel, O. discalis Cameron, O. gigantulus Fauvel, O. ginyuenensis Bernhauer, O. javanus Cameron, O. kalisi Bernhauer, O. kedirianus Cameron, O. lucens Bernhauer, O. lucidulus Cameron, O. mandibularis Cameron, O. megaceros Fauvel, O. nilgiriensis Cameron, O. subferrugineus Cameron, O. subincisus Cameron, O. sublucidus Cameron, O. subsculptus Cameron, O. antennalis Fauvel (New Caledonia, New Guinea and Australia), O. cheesmani Bernhauer (New Hebrides), O. cheesmanianus Cameron (Papua New Guinea), O. hingstoni Cameron (India), and O. tibetanus Bernhauer (China). The species O. (Anotylus) transversipennis Scheerpeltz is transferred to the genus Anotylus. Other than the new species, nine previously known species are redescribed, a key to 30 species and line drawings or color photographs of 42 species are provided. Thus, a total of 30 species are recorded from Southeast Asia.